Understanding the patterns and predictors of elevated psychological distress among humanitarian migrants compared to the host population: comparative matched analysis using two national data sources from Australia - Demelash Woldeyohannes Handiso; Jacqueline A. Boyle; Eldho Paul; Frances Shawyer; Graham Meadows; Joanne C. Enticott (Epidemiology and Psychiatric Sciences, 2025)
Abstract Aims Understanding patterns and predictors of elevated psychological distress (EPD) among humanitarian migrants compared to the host population is critical for designing effective mental health interventions. However, existing research presents conflicting findings on the prevalence of EPD. This study examined EPD prevalence and associated factors in humanitarian migrants and Australian-born adults using large population-level datasets.